When Minsky and Godley met structuralism: A stock-flow consistent approach to the currency hierarchy - Nitin Nair (Levy Economics Institute of Bard College, 2023)
Underdevelopment is often conceived as being reproduced domestically. This paper emphasizes the international forces that enable the persistence of underdevelopment. We first explore how the currency hierarchy imposes a dependency relation between developed and underdeveloped economies. We improvise and quantify the currency hierarchy using ratios from the consolidated sovereign balance sheet. Using the improvisation of the currency hierarchy, we identify that a weak currency must compensate its position by resorting to three mechanisms: changes in interest rates, changes in exchange rates, and accumulation of international reserves to improve balance sheet structure. We employ these relationships to formulate two novel, financial postKeynesian behavioral equations: an international reserves function and a domestic interest rate function. These equations are simulated in a stock-flow consistent model. We simulate the transmission of international shocks and domestic fiscal expansion. The key findings are (1) that the intensity of economic activity in the emerging economy is reliant on the level of economic activity (and policy) i n the developed economy and (2) that any attempts to stimulate-through government spending-the emerging economy benefit primarily the developed economy while harming the emerging economy's private sector, assuming free capital and goods mobility. This indicates the existence of a balance-of-payment constrained expansion originating from the demand for international reserves as a margin of safety. Simulations show import controls to be a solution. We find government spending complemented by import substitution to be the most appropriate response to a crisis of international origin and suggest the need for international cohesion between emerging economies to create a more conducive international financial and trade system, halting the reproduction of underdevelopment.
Keywords: E12; F30; O11; O23; E00; 330; Minsky; Godley; Stock-Flow Modeling; Structuralism; Currency Hierarchy; Balance-of-Payment Constraint; International Reserves